Bacteriological and clinical studies on cefluprenam in the field of surgery - Shinagawa, Nagao; Mizuno, Akira; Hisada, Masazumi; Yura, Jiro; Ishikawa, Shu; Mashita, Keiji (Japanese Journal of Chemotherapy, 1995)
We performed bacteriological and clinical studies on cefluprenam, a new parenteral cephalosporin antibiotic, in the field of surgery to determine its antibacterial activity and clinical efficacy.The results were as follows: (1) Antibacterial activity: The MIC50/MIC90 values (μg/ml) of cefluprenam against surgical lesion isolates of Staphylococcus aureus, Escherichia coil, Klebsiella pneumoniae, and Pseudomonas aeruginosa were 25/50, ≤0.2≤0.2, ≤0.2≤0.2, 1.56/12.5, respectively. (2) Transport to bile: After intravenous administration of cefluprenam (1 g) to 2 subjects, its maximum concentration in bile was 22.0μg/ml and 6.35μg/ml. (3) Clinical efficacy: In 5 patients with surgical infections treated with cefluprenam, the response was excellent in 1 patient, good in 2 and fair in 1.In the bacteriological study, the causative pathogens were isolated from 3 patients and eradicated in 2, replaced in 1, and unknown in 2 cases.Neither subjective nor objective side effects were observed.Abnormal laboratory test findings were observed in 1 case with elevated GOT, GPT and ALP.